GV m−1 on-chip particle accelerator driven by few-cycle femtosecond laser pulse - Li Sun; Weihao Liu; Jie Zhou; Yunliang Zhu; Zijia Yu; Yucheng Liu; Qika Jia; Baogen Sun; Hongliang Xu (New Journal of Physics, 2021)
Particle accelerator on chip with high acceleration gradient has been an unremitting goal of researchers. Dielectric laser accelerator (DLA) is a possible candidate to achieve this goal. However, due to the limitation of dielectric breakdown, it is difficult for the available DLAs to reach an acceleration gradient as high as 1 GV m ^−1 since a long-duration multi-cycle laser pulse with high fluence have to be used. Here we propose to use a few-cycle laser pulse to drive a DLA based on the inverse Cherekov radiation effect. It significantly reduces the required pulse duration and the laser fluence, remarkably increasing the achievable acceleration gradient. Moreover, by using a cascade acceleration scheme, we realize a high energy-gain acceleration for low-energy electrons in a microscale device by simulation, which paves the way for the development of a fully on-chip particle accelerator.